2021
DOI: 10.3390/ijerph18073462
|View full text |Cite
|
Sign up to set email alerts
|

Does Delaying Time in Cancer Treatment Affect Mortality? A Retrospective Cohort Study of Korean Lung and Gastric Cancer Patients

Abstract: The aim of this study is to investigate the association between delays in surgical treatment and five- and one- year mortality in patients with lung or gastric cancer. The National Health Insurance claims data from 2006 to 2015 were used. The association between time to surgical treatment, in which the cut-off value was set at average time (30 or 50 days), and five year mortality was analyzed using the Cox proportional hazard model. Subgroup analysis was performed based on treatment type and location of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Wang et al showed that good perioperative nursing might boost postoperative recovery of patients and improve prognosis [ 6 ]. Nonetheless, conventional nursing fails to alleviate the patients' adverse emotions and leads to compromised treatment efficacy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al showed that good perioperative nursing might boost postoperative recovery of patients and improve prognosis [ 6 ]. Nonetheless, conventional nursing fails to alleviate the patients' adverse emotions and leads to compromised treatment efficacy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the shortcomings of chemotherapy, traditional Chinese medicine (TCM), such as acupuncture, TCM herbal compression, and herbal decoction, is encouraged as adjuvant therapy to reduce toxicity of chemotherapy drugs and enhance treatment e cacy [5]. Wang et al showed that good perioperative nursing might boost postoperative recovery of patients and improve prognosis [6]. Nonetheless, conventional nursing fails to alleviate the patients' adverse emotions and leads to compromised treatment e cacy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we observed a prominent difference in admission patterns before and during the COVID-19 period. Many factors resulted in prolonged preoperative waiting times before the COVID-19 pandemic, such as holidays, underlying diseases, diagnosis level of the hospital at the time, and rotation rate of hospital beds ( 20 , 21 ). However, the delay caused by the COVID-19 pandemic made the previous experience of delayed surgery related to waiting time no longer as effective as before, which varied in different countries with different policies and severity of the local pandemic ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the Netherlands showed that waiting time for any treatment (neoadjuvant chemotherapy or gastrectomy) was not associated with lower overall survival ( 26 ). A study in Asia reported that it was safe to wait for surgery for one–two more weeks ( 21 , 27 ). Since there are no SARS-CoV-2 infected cases in our study, no SARS-CoV-2 infection bias was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the effects of prolonged curtailing of lung cancer screening have yet to be determined, it is known that delay in diagnosis and treatment of lung cancer affects the survival of patients. [48][49][50] Although only a modest impact on survival may be the case if the pandemic were short-lived, the prolonged pandemic of over 18 months now and the observed reduction in the number of resectable early-stage lung cancers suggest that we will be seeing more advanced lung cancers in the coming months and years with prominent effects on mortality. It is, therefore, crucial to find a solution to continue lung cancer screening even with reduced health care resources, taking into account multiple local, regional, and patient-related factors to provide optimal care.…”
Section: February 2022mentioning
confidence: 99%